Kefir peptides attenuate atherosclerotic vascular calcification and osteoporosis in atherogenic diet-fed ApoE−/− knockout mice - Chang, Gary Ro-Lin; Cheng, Wei-Yuan; Fan, Hueng-Chuen; Chen, Hsiao-Ling; Lan, Ying-Wei; Chen, Ming-Shan; Yen, Chih-Ching; Chen, Chuan-Mu (Frontiers in Cell and Developmental Biology, 2023)
Aims: Vascular calcification (VC) and osteoporosis were previously considered two distinct diseases. However, current understanding indicates that they share common pathogenetic mechanisms. The available medicines for treating VC and osteoporosis are limited. We previously demonstrated that kefir peptides (KPs) alleviated atherosclerosis in high-fat diet (HFD)-induced apolipoprotein E knockout (ApoE−/−) mice. The present study further addressed the preventive effects of KPs on VC and osteoporosis in ApoE−/− mice fed a high-cholesterol atherogenic diet (AD). Main methods: Seven-week-old ApoE−/− and wild-type C57BL/6 mice were randomly divided into five groups (n = 6). The development of VC and osteoporosis was evaluated after AD feeding for 13 weeks in KP-treated ApoE−/− mice and compared to C57BL/6 and ApoE−/− mice fed a standard chow diet (CD). Key findings: The results indicated that KP-treated ApoE−/− mice exhibited lower serum total cholesterol, oxidized low-density lipoprotein (ox-LDL), malondialdehyde (MDA) levels, and serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and creatine kinase (CK) activities, which suggested that KPs prevented hyperlipidemia and possible damages to the liver and muscle in ApoE−/− mice. KPs reduced serum tumor necrosis factor-α (TNF-α) and the local expression of TNF-α, IL-1β, and macrophage-specific CD68 markers in aortic tissues, which suggested that KPs inhibited inflammatory responses in AD-fed ApoE−/− mice. KPs reduced the deposition of lipid, collagen, and calcium minerals in the aortic roots of AD-fed ApoE−/− mice, which suggested that KPs inhibited the calcific progression of atherosclerotic plaques. KPs exerted osteoprotective effects in AD-fed ApoE−/− mice, which was evidenced by lower levels of the bone resorption marker CTX-1 and higher levels of the bone formation marker P1NP. KPs improved cortical bone mineral density and bone volume and reduced trabecular bone loss in femurs. Significance: The present data suggested that KPs attenuated VC and osteoporosis by reducing oxidative stress and inflammatory responses in AD-fed ApoE−/− mice. Our findings contribute to the application of KPs as preventive medicines for the treatment of hyperlipidemia-induced vascular and bone degeneration.